Optimal Motherhood and Other Lies Facebook Told Us Assembling the Networked Ethos of Contemporary Maternity Advice - Clements, Jessica (The MIT Press, 2022)
An exploration of social media-imposed pressure on new mothers: How the supposed safe havens of online mommy groups have become rife with aggression and groupthink. Many mothers today turn to social media for parenting advice, joining online mothers' groups on Facebook and elsewhere. But the communities they find in these supposed safe havens can be rife with aggression, peer pressure, and groupthink-insisting that only certain practices are "best," "healthiest," "safest" (and mandatory). In this book, Jessica Clements and Kari Nixon debunk the myth of "optimal motherhood"-the idea that there is only one right answer to parenting dilemmas, and that optimal mothers must pursue perfection. In fact, Clements and Nixon write, parenting choices are not binaries, and the scientific findings touted by mommy groups are neither clear-cut nor prescriptive. Clements and Nixon trace contemporary ideas of optimal motherhood to the nineteenth-century "Cult of True Womanhood," which viewed women in terms of purity and dignity. Both mothers themselves, they joined a variety of Facebook mothers' groups to explore what goes on in online mommy wars. They examine debates within these groups over CDC recommendations about alcohol during pregnancy, birth plans that don't go according to plan, breastfeeding vs. formula, co-sleeping and "crying it out," and "tweaking" pregnancy test kits to discern pregnancy as early as possible. Clements and Nixon argue for an empowered motherhood, freed from the impossible standards of the optimal.